Re-contact Following Withdrawal of Minors from Research - Patrinos, Dimitri; Knoppers, Bartha; Kleiderman, Erika; Rahbari, Noriyeh; Laplante, David; Wazana, Ashley (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
Re-contacting minors enrolled in research upon their reaching the age of majority or maturity to seek their autonomous consent to continue their participation is considered an ethical requirement. This issue has generally been studied in the context of minors who are actively involved in the research. However, what becomes of this issue when the minor has been withdrawn from the research or has been lost to follow-up? May researchers re-contact the minor at the age of majority or maturity under these circumstances to seek the consent of the minor to re-join the research? In this paper, we explore the ethical permissibility of recontacting minors whose participation in research has ended, once they have reached the age of majority or maturity. In particular, we identify scenarios in which the participation of a minor in a research project may end and discuss factors that can help determine such an ethical permissibility. Finally, we discuss the practical and ethical challenges of re-contact and present re-consent models that may be used by researchers.